(untitled) (Scientia Agropecuaria, 2021)
Oregmopyga peruviana, pest of the V. vinifera, reduces the production of the grape and in strong infestations provokes the death of the plant. The research aimed to obtain information on the life cycle, biological behavior, host plants and biological control agents of the pest through laboratory and field observation, through descriptive analysis. O. peruviana was determined to have a life cycle of 22.4 ± 2.06 days, with an oviposition capacity of 12.6 ± 1.9 eggs*female-1, incubation period of 5.5 ± 0.52 days and nymphal period of 16.8 ± 2.13 days; biological behavior, nymphs are mobile and adult females are stationary, sensitive to the alteration of its habitat and die when the bark is removed. No host plants were found, highlights the presence of a parasite insect (Hymenoptera: Encyrtidae), a predator Sympherobius sp. (Neuroptera: Hemerobiidae), and Pyroderces sp. (Lepidoptera: Cosmopterigidae). The results show that O. peruviana is a specific V. vinifera pest and only attacks exclusively below the bark of trunks and branches lignified, being the nymphs apparently the colonizers. O. peruviana has native biological control agents.